Rethinking personhood and agency: how AI challenges human-centered concepts - Gao, Lu; Mvondo, Gustave Florentin Nkoulou (Frontiers in Psychology, 2026)
Artificial intelligence (AI) systems increasingly display behaviors once thought to be exclusively human, prompting people to attribute intention, emotion, and even moral responsibility to these agents. This philosophical perspective examines how psychology understand and respond to these developments in human-AI interaction: How and why do humans perceive and attribute personhood and agency to AI systems, what are the personal and social consequences of doing so, and what are the implications for psychology as a discipline? We thus advocate that psychology adopt an experience-focused approach to human-AI interactions, drawing primarily on psychological research related to the sense of agency and related aspects of self-experience. From this discussion, we develop a three-lens framework (explanatory, normative, and cultural) as a guide for advancing psychological research and practices related to human-AI interactions. We propose that psychology’s distinctive contribution in the age of AI is to analyze how concepts of agency and personhood function in lived human experience, particularly in shaping perceptions of control and responsibility regarding AI systems.